Glucose Induces ECF Sigma Factor Genes, sigX and sigM, Independent of Cognate Anti-sigma Factors through Acetylation of CshA in Bacillus subtilis - Ogura, Mitsuo; Asai, Kei (Frontiers in Microbiology, 2016)
Extracytoplasmic function (ECF) σ factors have roles related to cell envelope and/or cell membrane functions, in addition to other cellular functions. Without cell-surface stresses, ECF σ factors are sequestered by the cognate anti-σ factor, leading to inactivation and the resultant repression of regulons due to the inhibition of transcription of their own genes. B. subtilis has seven ECF σ factors including σX and σM that transcribe their own structural genes. Here, we report that glucose addition to the medium induced sigX and sigM transcription independent of their anti-σ factors. This induction was dependent on an intracellular acetyl-CoA pool. Transposon mutagenesis searching for the mutants showing no induction of sigX and sigM revealed that the cshA gene encoding DEAD-box RNA helicase is required for gene induction. Global analysis of the acetylome in B. subtilis showed CshA has two acetylated lysine residues. We found that in a cshA mutant with acetylation-abolishing K to R exchange mutations, glucose induction of sigX and sigM was abolished and that glucose addition stimulated acetylation of CshA in the wild type strain. Thus, we present a model wherein glucose addition results in a larger acetyl-CoA pool, probably leading to increased levels of acetylated CshA. CshA is known to associate with RNA polymerase (RNAP), and thus RNAP with acetylated CshA could stimulate the autoregulation of sigX and sigM. This is a unique model showing a functional link between nutritional signals and the basal transcription machinery.